The Influence of Digital Marketing Strategy and Product Innovation on Culinary Business Income - Oscarius Yudhi Ari Wijaya (Yayasan Riset dan Pengembangan Intelektual, 2022)
The research aims to determine the effect of digital marketing strategy and product innovation on culinary business income in Surabaya. The research method used is descriptive verification method with a survey approach. The population in this study are culinary entrepreneurs in Surabaya whose number is unknown. Samples were taken by accidental sampling so that a total of 100 people were obtained based on the Slovin method. Data were analyzed using IBM SPSS version 26 and data analysis through several tests, namely: validity test, reliability test, classical assumption test, multiple linear regression analysis and coefficient of determination test. The results of this research show that digital marketing strategies and product innovation have a positive and significant effect on culinary business income in Surabaya.